MiR-488-3p Protects Cardiomyocytes against Doxorubicin-Induced Cardiotoxicity by Inhibiting CyclinG1. (10th February 2022) - Yan, Mingjing; Cao, Yuan; Wang, Que; Xu, Kun; Dou, Lin; Huang, Xiuqing; Chen, Beidong; Tang, Weiqing; Lan, Ming; Liu, Bing; Zhu, Kaiyi; Yang, Yao; et al.
Abstract : Objective . To investigate the protective effects and regulatory mechanism of miR-488-3p on doxorubicin-induced cardiotoxicity. Methods . The C57BL/6 mice and primary cardiomyocytes were used to construct doxorubicin-induced cardiomyocyte injury models in vivo and in vitro. The levels of miR-488-3p and its downstream target genes were analyzed by quantitative real-time PCR. Mouse cardiac function, cell survival, cellular injury-related proteins, and the apoptosis level of cardiomyocytes were analyzed by echocardiography, MTT analysis, Western blotting, and DNA laddering separately. Results . Cardiomyocyte injury caused by a variety of stimuli can lead to the reduction of miR-488-3p level, especially when stimulated with doxorubicin. Doxorubicin led to significant decrease in cardiac function, cell autophagic flux blockage, and apoptosis in vivo and in vitro. The expression of miR-488-3p's target gene, CyclinG1, increased remarkably in the doxorubicin-treated neonatal mouse cardiomyocytes. Overexpression of miR-488-3p inhibited CyclinG1 expression, increased cardiomyocyte viability, and attenuated doxorubicin-induced cardiomyocyte autophagic flux blockage and apoptosis. Conclusions . miR-488-3p is one of the important protective miRNAs in doxorubicin-induced cardiotoxicity by inhibiting the expression of CyclinG1, which provides insight into the possible clinical application of miR-488-3p/CyclinG1 as therapeutic targets in doxorubicin-induced cardiovascular diseases.